(3QSGdI aj WHjYI GdEfSGfs - (3CHh SdjeGfs
(3ChdgG (B:s
(3GdWHjYI GSe eTJQc jOd Ydi eYGf CMOgG PGJ cd TF YQVkG cGf Ch LhgQkG hHSjWkG cGf Ch eQcHkG s
(3BNQgG (B:s
(3aEf GdefWb dGjedc CWdH GdMb HGdYbd OGFekG JSde OgQc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs